Loneliness and emotion regulation. (October 2021) - Preece, David A.; Goldenberg, Amit; Becerra, Rodrigo; Boyes, Mark; Hasking, Penelope; Gross, James J.
Abstract: Loneliness is a risk factor for mental disorders and is a significant and growing public health issue, but to date, loneliness interventions have had limited success. We propose that an emotion regulation perspective might be useful for understanding loneliness and for suggesting new treatment targets. In this study, our aim was to test the basis for this proposal by examining whether individual differences in emotion regulation strategy use can explain significant variance in loneliness, and to establish what profile of strategy use might characterize loneliness. We administered a comprehensive battery of loneliness and emotion regulation questionnaires to 501 adults. In a regression model, emotion regulation strategy use accounted for over half (52.2%) the variance in loneliness. A latent profile analysis revealed four profiles, with the "high loneliness" profile characterized cognitively by greater use of rumination, catastrophising, blame-attribution, and lesser use of cognitive reappraisal type strategies. Behaviorally, loneliness was characterised by greater use of expressive suppression, and regulating emotions by actively rejecting or withdrawing from others. We conclude that individual differences in emotion regulation may play an important role in explaining loneliness, and could therefore represent a promising treatment target. Highlights: An emotion regulation framework may be useful for better understanding loneliness. In our study, regulation strategy use explained over half the variance in loneliness. Loneliness was characterized by a distinct profile of emotion regulation strategies. More use of rumination, catastrophising, blaming, suppression, and withdrawal Less use of cognitive reappraisal and active approaching of problems